2011
DOI: 10.1371/journal.pone.0029148
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium abscessus Glycopeptidolipid Prevents Respiratory Epithelial TLR2 Signaling as Measured by HβD2 Gene Expression and IL-8 Release

Abstract: Mycobacterium abscessus has emerged as an important cause of lung infection, particularly in patients with bronchiectasis. Innate immune responses must be highly effective at preventing infection with M. abscessus because it is a ubiquitous environmental saprophyte and normal hosts are not commonly infected. M. abscessus exists as either a glycopeptidolipid (GPL) expressing variant (smooth phenotype) in which GPL masks underlying bioactive cell wall lipids, or as a variant lacking GPL which is immunostimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 36 publications
(63 reference statements)
1
65
1
Order By: Relevance
“…A rough clinical isolate persisted in the lungs of experimentally infected mice and disseminated into the spleen, whereas a smooth isolate was cleared from the lungs within 3 weeks (16). An isogenic mutant of M. abscessus that lacked GPL production lost biofilm formation but gained the ability to replicate inside macrophages, stimulate Toll-like receptor 2, and induce cytokine production (17,18). It has also been suggested that the rough morphotype is more virulent in humans (19).…”
mentioning
confidence: 99%
“…A rough clinical isolate persisted in the lungs of experimentally infected mice and disseminated into the spleen, whereas a smooth isolate was cleared from the lungs within 3 weeks (16). An isogenic mutant of M. abscessus that lacked GPL production lost biofilm formation but gained the ability to replicate inside macrophages, stimulate Toll-like receptor 2, and induce cytokine production (17,18). It has also been suggested that the rough morphotype is more virulent in humans (19).…”
mentioning
confidence: 99%
“…We have previously verified the specificity of HβD2 as a readout for M. abscessus TLR2 stimulation by siRNA knockdown of TLR2 which abrogated HβD2 release in response to M. abscessus [6]. In addition, we have reported that phosphatidyl inositol mannosides (PIMs) are one of the M. abscessus ligands for TLR2.…”
Section: Resultsmentioning
confidence: 91%
“…These cells are among the various cell types which express toll-like receptors (TLRs); receptors which mediate the innate immune response to invading pathogens [3]. Both interleukin-8 (IL-8) and human β-defensin 2 (HβD2) are expressed by respiratory epithelial cells in response to TLR stimulation [46]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the hypothesis that GPL on the outer cell wall of M. abscessus allows the bacillus to initially avoid inducing immunity by avoiding TLR2 triggering, but when it is not present, this unmasks other materials, possibly phosphatidylinositol mannosides or lipoarabinomannans, that are known to be TLR2 agonists. More recently, disruption of the mmpL4b gene, which is involved in GPL biosynthesis, resulted in bacilli that could trigger TLR2 in macrophage cultures (85,86); these mutants lack GPL but also seem to upregulate the production of cell wall lipoproteins (87). What has yet to be explained, however, is why mechanisms other than TLR2 signaling do not compensate and prevent GPL Ϫ M. abscessus from so quickly killing mice.…”
Section: Immunity To M Abscessus An Emerging Pathogenmentioning
confidence: 99%